KAJIAN MANFAAT E-COMMERCE PADA PENJUALAN PRODUK USAHA â€œSNACKINGâ€ DI KOTA MANADO - Josua Julio Brenda Lumintang; Grace Adonia Josefina Rumagit; Melissa Lady Gisela Taroreh (AGRI-SOSIOEKONOMI, 2020)
This study aims to examine the benefits of e-commerce in selling "snacking" business products in the city of Manado. This research was conducted from May to June 2020. The data used in this study are primary data obtained through interviews with â€œSnackingâ€ business owners. The data collection method in this study is a survey method. The data analysis method used in this research is descriptive method with a quantitative approach, to describe the sales of "snacking" business products in utilizing e-commerce. The results showed that the benefits of e-commerce in selling "snacking" business products, which can help in increasing the number of orders and sales turnover, as well as a means of business promotion, as well as helping in the development of business products.